Prenatal labor analgesia education program on outcomes for primiparas: study protocol for a randomized controlled trial - Jiali Wu; Jing Chen; Weiwen Zhang; Jiangtao OuYang; Jia Li; Xujuan Zheng (BMC Public Health)
Abstract Background A significant number of primiparous women lack awareness of labor epidural analgesia, resulting in lower acceptance of labor epidural analgesia. Additional prenatal education may help primiparas understand labor epidural analgesia and increase labor epidural analgesia rates. This randomized controlled trial (RCT) will evaluate the effects of an online and offline prenatal labor epidural analgesia education program for primiparas to improve their labor epidural analgesia rate and to reduce their misunderstanding of labor epidural analgesia and fear of birth. Methods A single-blinded, randomized, controlled, parallel-design trial will be conducted. Based on the Theory of Planned Behavior, online and offline prenatal labor epidural analgesia education program has five modules: (a)elementary knowledge, (b)attitude, (c)subjective norm, (d) perceived behavioral control and (e)behavioral intention. Primiparous women will be recruited in the obstetrics department or midwife clinic of a tertiary hospital in Shenzhen, China. The participants (N = 196) will be randomly allocated to the intervention group (N = 98) that receives routine prenatal education and access to the online and offline prenatal labor epidural analgesia education program and the control group (N = 98) that receives routine prenatal education. Labor epidural analgesia rate will be extracted from the electronic medical record; misunderstanding and intention of labor epidural analgesia and fear of birth will be measured at baseline and immediately after the intervention. The study was ethically approved in November 2023. Discussion If the online and offline prenatal labor epidural analgesia education program has positive outcomes, it may offer an effective intervention program to decrease misperceptions of labor epidural analgesia and fear of birth and to improve the labor epidural analgesia rate for Chinese primiparas. As the first RCT study to evaluate the effect of the online and offline prenatal labor epidural analgesia education program with a strict research design and a theoretical framework, this research will provide evidence on prenatal labor analgesia health education for clinical practice in China. Trial Registration Registered at the Chinese Clinical Trials.gov on January 11th, 2024. Trial Registration Number: ChiCTR2400079767.